Characteristics of Social Networks and Mortality Risk: Evidence From 2 Prospective Cohort Studies. Issue 4 (23rd August 2017) - Kauppi, Maarit; Kawachi, Ichiro; Batty, George David; Oksanen, Tuula; Elovainio, Marko; Pentti, Jaana; Aalto, Ville; Virtanen, Marianna; Koskenvuo, Markku; Vahtera, Jussi; Kivimäki, Mika
Abstract: The size of a person's social network is linked to health and longevity, but it is unclear whether the number of strong social ties or the number of weak social ties is most influential for health. We examined social network characteristics as predictors of mortality in the Finnish Public Sector Study ( n = 7, 617) and the Health and Social Support Study ( n = 20, 816). Social network characteristics were surveyed at baseline in 1998. Information about mortality was obtained from the Finnish National Death Registry. During a mean follow-up period of 16 years, participants with a small social network (≤10 members) were more likely to die than those with a large social network (≥21 members) (adjusted hazard ratio (HR) = 1.23, 95% confidence interval (CI): 1.04, 1.46). Mortality risk was increased among participants with both a small number of strong ties (≤2 members) and a small number of weak ties (≤5 members) (HR = 1.55, 95% CI: 1.26, 1.79) and among participants with both a large number of strong ties and a small number of weak ties (HR = 1.28, 95% CI: 1.08, 1.52), but not among those with a small number of strong ties and a large number of weak ties (HR = 1.04, 95% CI: 0.87, 1.25). These findings suggest that in terms of mortality risk, the number of weak ties may be an important component of social networks.